2010
DOI: 10.1143/jjap.49.04dk09
|View full text |Cite
|
Sign up to set email alerts
|

Development of Field-Effect Transistor-Type Photorewritable Memory Using Photochromic Interface Layer

Abstract: We developed a novel field-effect transistor (FET) type photorewritable memory using a photochromic interface layer between the active layer and the gate insulator layer. A diarylethene (DAE) derivative was employed as a photochromic material and pentacene was employed as an active layer. DAE has two types of photoisomer, i.e., the closed- and open-ring isomers. In this study, it was clarified that the highest occupied molecular orbital (HOMO) level of the closed-ring DAE worked as an interfacial deep trap lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…Similar to DAE_Me, it is possible that DAE_tBu does not interfere with the polycrystalline domains but locates in the amorphous regions of P3HT. Moreover, previous reports on combining another DAE derivative with a small molecule, such as pentacene, showed that the HOMO level of the ring-open isomer did not act as a trap level 11 , which is in agreement with our results for P3HT with DAEs. However, for -300 …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Similar to DAE_Me, it is possible that DAE_tBu does not interfere with the polycrystalline domains but locates in the amorphous regions of P3HT. Moreover, previous reports on combining another DAE derivative with a small molecule, such as pentacene, showed that the HOMO level of the ring-open isomer did not act as a trap level 11 , which is in agreement with our results for P3HT with DAEs. However, for -300 …”
Section: Resultssupporting
confidence: 93%
“…However, thin films made solely from DAEs suffer from rather poor charge transport properties. This problem can be solved by blending the DAE with organic (semi)conductors such as carbon nanotubes 10 , pentacene 11 or poly(3-hexylthiophene) (P3HT) 12 to combine the light-responsive nature of the DAE with the advantageous charge transport characteristics of the respective matrix component. We have recently shown that by blending DAE and P3HT in solution-processed bi-component films, the P3HT forms polycrystalline structures, while the DAE is dispersed in the less aggregated regions of the polymer film 12 .…”
mentioning
confidence: 99%
“…These features can be optimized by achieving control over the packing of SAMs on the NPs (7). When NPs are integrated in a device, they can, for example, act as charge storage sites-i.e., trapping charges centers, allowing the system to act as a memory (9, 10).The incorporation of photochromic molecules into electronic devices to confer them a photoresponsive nature has been recently explored (11)(12)(13)(14). Among photochromic systems (15-18), azobenzene derivatives are known to undergo isomerization from trans to cis form, and vice versa, under illumination at a specific wavelength, as well as from cis to trans with temperature (15).…”
mentioning
confidence: 99%
“…The incorporation of photochromic molecules into electronic devices to confer them a photoresponsive nature has been recently explored (11)(12)(13)(14). Among photochromic systems (15)(16)(17)(18), azobenzene derivatives are known to undergo isomerization from trans to cis form, and vice versa, under illumination at a specific wavelength, as well as from cis to trans with temperature (15).…”
mentioning
confidence: 99%
“…While carrier mobilities in these molecules have been found to be too low so far for an efficient application of the neat materials [4], promising device perspectives have been achieved upon doping high-mobility organic semiconductors with photo-switchable small molecules (PSMs). To name only a few, the ON/ OFF ratio of organic field-effect transistors can be optically tuned with PSMs at the metal contact or by direct mixing with the active semiconductor [5,6]; blending dielectric materials with PSMs has been used to optically modulate their gate capacitance [7] and even "photo-programmable" organic light-emitting diodes have been realized with PSM-doped hole injection layers [8].…”
Section: Introductionmentioning
confidence: 99%